Economic aspects of Bantu migrant labour : an investigation into conditions in Pretoria and the Northern Transvaal - Leistner, G. M. E.(Gerhard Max Erich) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1963.